Phenotypic characterization of drug resistance and tumor initiating cancer stem cells from human bone tumor osteosarcoma cell line OS-77 (Bangladesh Journal of Pharmacology, 2014)
The cancer stem cell theory suggest that presence of small subpopulation of cancer stem cells are the major implication in the cancer treatment and also responsible for tumor recurrence. Based on Hoechst 33342 dye exclusion technique, we have identified about 3.3% of cancer stem like side population (SP) cells from human osteosarcoma OS-77 cell line whose prevalence is significantly reduced to 0.3% after treatment with verapamil. The sphere formation assay revealed that osteosarcoma SP cells are highly capable to form tumor spheres (sarcospheres). Further by immunocytochemistry and RT-PCR, we show that OS-77 SP cells have enhanced expression of stem cell surface markers such as CD44, Nanog and ATP-binding cassette (ABC) transporter gene (ABCG2) which contributes to self-renewal and drug resistance, respectively. Our findings help to designing a novel therapeutic drug which could effectively target the cancer stem cells and prevent the tumor relapse.